Science teacher candidates' awareness and behaviors regarding biodiversity: Scale development study - Özyurt, Zeynep; Turkoglu, İsmail; Cırıt, Didem Karakaya (My University, 2025)
The aim of this study was to develop a scale to determine the awareness and behavior levels of pre-service science teachers regarding biodiversity. A pool of 60 items for the measurement tool was created through a literature review conducted by the researcher. After obtaining expert opinions, the number of items was reduced to 56 and revised accordingly. The prepared scales were administered to 280 students at two public universities. Exploratory factor analysis (EFA) was conducted to assess the construct validity of the scale. The 'Biodiversity Awareness Measurement Tool' (BAMT) was finalized with 24 items based on the EFA results, while the 'Biodiversity Behavior Measurement Tool' (BBMT) was finalized with 25 items. After the reliability study, the overall Cronbach's alpha coefficient for BAMT was found to be .72, and for BBMT, it was .75. As a result of all these studies, a 5-point Likert-type scale consisting of 24 items prepared in 6 sub-dimensions to measure biodiversity awareness levels and a scale consisting of 25 items prepared in 7 sub-dimensions to measure biodiversity behavior levels were developed.
Keywords: Biodiversity; Behavior; Awareness; Teachers Candidate